Strategi Kepolisian Resort Kabupaten Keerom dalam Mewujudkan Keamanan Berbasis Kearifan Lokal - Tianto, Agus; Sapioper, Hiskia C.M. (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze police strategies in realizing local wisdom-based security in Keerom Regency through the integration of community cultural values. This study is urgent as local wisdom integration is vital for sustainable peace and trust in Papua. The research method used is a qualitative approach with an in-depth case study. The research location was carried out in the Papua region, where the richness of local wisdom is a primary asset. Data collection techniques were carried out through in-depth interviews, field observations, and analysis of policy documents. Research informants included police officers, traditional leaders, and academics who understand the dynamics of security and local cultural values. Research instruments in the form of interview guidelines and observation sheets were developed to obtain valid data. Data analysis was conducted using thematic analysis techniques to identify interaction patterns, obstacles, and potential synergies between officers and the community. The results of the study revealed that the integration of local wisdom in police strategies can increase public trust and the effectiveness of law enforcement, although there are still obstacles in the understanding of culture by officers. The discussion shows that a participatory approach and collaboration between officers and traditional leaders are key to success. The conclusion of the study emphasizes the need to increase the capacity of officers through cultural training and strengthening cross-sectoral cooperation. The recommendations from the research results are expected to serve as a reference in developing security policies in conflict areas such as Papua.This study aims to analyze police strategies in realizing local wisdom-based security in Keerom Regency through the integration of community cultural values. This study is urgent as local wisdom integration is vital for sustainable peace and trust in Papua. The research method used is a qualitative approach with an in-depth case study. The research location was carried out in the Papua region, where the richness of local wisdom is a primary asset. Data collection techniques were carried out through in-depth interviews, field observations, and analysis of policy documents. Research informants included police officers, traditional leaders, and academics who understand the dynamics of security and local cultural values. Research instruments in the form of interview guidelines and observation sheets were developed to obtain valid data. Data analysis was conducted using thematic analysis techniques to identify interaction patterns, obstacles, and potential synergies between officers and the community. The results of the study revealed that the integration of local wisdom in police strategies can increase public trust and the effectiveness of law enforcement, although there are still obstacles in the understanding of culture by officers. The discussion shows that a participatory approach and collaboration between officers and traditional leaders are key to success. The conclusion of the study emphasizes the need to increase the capacity of officers through cultural training and strengthening cross-sectoral cooperation. The recommendations from the research results are expected to serve as a reference in developing security policies in conflict areas such as Papua.